(untitled) (Bioscience Journal, 2016)
Methyl jasmonateÂ (MeJA) is a lipid-derived plant hormone that mediates diverse biological phenomena. Application of MeJA onto rice spikelet could exhibit abnormal floral organ development. Although jasmonic acid (JA) has been proved to be involved in maize tassel sex determination process, the roles of JA and its precursor MeJA in maize tassel development still remain obscure. In this study, we found that tassel development was decelerated by application of2 mMMeJA. Exogenous MeJA also influenced the number of palea and stamens of tassel spikelets. Exogenous MeJA increased the expression level of some key regulator genes, which may responsible for the phenotypic change in MeJA-treated tassel, and may mediate the crosstalk between MeJA and other hormones.